CONTROL CHART AS VERIFICATION TOOLS IN TIME SERIES MODEL - Imro'ah, Nurfitri; Huda, Nur'ainul Miftahul (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Control charts are generally use in quality control processes, especially in the industrial sector, because they are helpful to increase productivity. However, control charts can also be used in time series analysis. The residuals from the time series model are used as observations in constructing the control chart. Because there is only one variable observed, namely the residual, the control chart used is the Individual Moving Range (IMR). This study analysis the accuracy of the time series model using the IMR control chart in two models, namely the Autoregressive Distributed Lag (ADL) model without outliers and the ADL model with outliers. The results showed that the control chart could be used to measure the accuracy of the time series model. The accuracy of the model can be seen from the statistically controlled residual (in control).